Anti-Alcohol and Anxiolytic Properties of a New Chemical Entity, GET73 - Loche, Antonella; Simonetti, Francesco; Lobina, Carla; Carai, Mauro A.; Colombo, Giancarlo; Castelli, Paola; Barone, Domenico; Cacciaglia, Roberto (Frontiers in Psychiatry, 2012)
N-[(4-trifluoromethyl)benzyl]4-methoxybutyramide (GET73) is a newly synthesized compound structurally related to the clinically used, alcohol-substituting agent, gamma-hydroxybutyric acid (GHB). The present study was designed to assess whether GET73 may share with GHB the capacity to reduce alcohol intake in rats. Additionally, the effect of treatment with GET73 on anxiety-related behaviors and cognitive tasks in rats was investigated. A series of in vitro binding assays investigated the capacity of GET73 to bind to the GHB binding site and multiple other receptors. GET73 (10-9-10-3 M) failed to inhibit [3H]GHB binding at both high- and low-affinity GHB recognition sites in rat cortical membranes. GET73 displayed minimal, if any, binding at dopamine, serotonin , GABA, and glutamate receptors in membranes from different rat brain areas. Acute treatment with low-to-moderate, non-sedative doses of GET73 (5-50 mg/kg, i.g. or i.p.) (a) reduced alcohol intake and suppressed “alcohol deprivation effect” (a model of alcohol relapse) in selectively bred, Sardinian alcohol-preferring (sP) rats, (b) exerted anxiolytic effects in Sprague-Dawley (SD) and sP rats exposed to the Elevated Plus Maze test, and (c) tended to induce promnestic effects in SD rats exposed to a modified water version of the Hebb-Williams maze test. Although the mechanism of GET73 action is currently unknown, the results of the present study suggest that GET73 has a multifaceted pharmacological profile, including the capacity to reduce alcohol drinking and anxiety-related behaviors in rats.